2017
DOI: 10.18295/squmj.2016.17.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Innervation of the Median Nerve in the Arm in the Absence of the Musculocutaneous Nerve

Abstract: abstract:The brachial plexus innervates the upper extremities. While variations in the formation of the brachial plexus and its terminal branches are quite common, it is uncommon for the median nerve to innervate the muscles of the arm. During the dissection of an elderly male cadaver at the Department of Anatomy, All India Institute of Medical Sciences, New Delhi, India, in 2016, the coracobrachialis muscle was found to be supplied by a direct branch from the lateral root of the median nerve and the musculocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In a proximal MN injury, a variation of an absent MCN may not only result in typical MN palsy of the forearm and hand, but also palsy in the arm that manifests as deficiencies in both shoulder and elbow flexion, as well as cutaneous sensory loss of the lateral forearm. 35 36…”
Section: Musculocutaneous Nervementioning
confidence: 99%
“…In a proximal MN injury, a variation of an absent MCN may not only result in typical MN palsy of the forearm and hand, but also palsy in the arm that manifests as deficiencies in both shoulder and elbow flexion, as well as cutaneous sensory loss of the lateral forearm. 35 36…”
Section: Musculocutaneous Nervementioning
confidence: 99%
“…the musculocutaneous nerve. The median nerve has been often found to supply the flexor muscles of arm in case of deficiency or damage to musculocutaneous nerve [10,11]. Sung-Yoon Won [12] observed 4 types of innervation of brachialis muscle in his study ranging from a single, double or triple innervation pattern by musculocutaneous, radial and median nerves.…”
Section: Case Reportmentioning
confidence: 99%
“…4 Anomalies are increasingly reported in the medical literature, as exemplified by a series of case reports and interesting medical images featured in the August 2016, November 2016 and February 2017 issues of SQUMJ. [5][6][7][8][9] This in turn suggests that there are still many discoveries to make in the field of anatomy. While such anomalies are rare, their recognition has important implications for diagnosis and treatment.…”
mentioning
confidence: 99%
“…13 Raza et al reported a case in which the musculocutaneous nerve was found to be absent during a routine dissection session. 8 The median nerve innervated all of the flexor muscles of the forearm, except for the coracobrachialis muscle, and branched into the lateral cutaneous nerve of the left forearm. The coracobrachialis muscle was innervated by a branch of the lateral root of the median nerve.…”
mentioning
confidence: 99%
See 1 more Smart Citation